2020
DOI: 10.1653/024.103.0221
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Development of Fall Armyworm (Lepidoptera: Noctuidae) in Weeds During the Off-Season

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Families and plant species that can be eaten by the larvae of S. frugiperda in this study are included in the families found by [8] stating that S. frugiperda can attack 78 plant families, including Poaceae and Convolvulaceae. For monocots, 13 plant species eaten by S. frugiperda larvae in this study were the host plants according to the research results, such as [13,15]. The leaves of 15 species of dicot plants eaten by S. frugiperda larvae were also reported by other studies, such as [19][20][21] as host plants of S. frugiperda.…”
Section: Resultssupporting
confidence: 68%
“…Families and plant species that can be eaten by the larvae of S. frugiperda in this study are included in the families found by [8] stating that S. frugiperda can attack 78 plant families, including Poaceae and Convolvulaceae. For monocots, 13 plant species eaten by S. frugiperda larvae in this study were the host plants according to the research results, such as [13,15]. The leaves of 15 species of dicot plants eaten by S. frugiperda larvae were also reported by other studies, such as [19][20][21] as host plants of S. frugiperda.…”
Section: Resultssupporting
confidence: 68%
“…This can be explained by the fact that mechanical weeding, which was the common weeding practice observed, could have mechanically damaged the pupae, exposed the pupae in the soil to harsh weather conditions, including direct sun heat and predators by removing the shading effect of the weeds. Weeds are known to be FAW reservoirs; this has been demonstrated in Brazil [ 54 ]. Although these weeds may also host FAW’s natural enemies [ 55 ], they may also host other pests, including cereal stemborers with which FAW share the same ecological niche and may contribute to the damage inflicted on the maize plants [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in recent studies difficulty in controlling A. hybridus due the resistance to glyphosate, the main herbicide used for its control (García et al, 2020;Resende et al, 2022). Besides that, these plants can remain in crops becoming a green bridge for herbivorous insects that damage crops of interest reducing producer profit (Moraes et al, 2020).…”
Section: Author's Contributionsmentioning
confidence: 99%